Virtual Tour Method as an Alternative Tourism Experience During The Covid-19 Pandemic (Case Study of Villages Nglanggeran, Yogyakarta) - Nuryadina Augusrini; Yanti Suzana; Novi Handayani; Rhamadeta Thasya Putri (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: The aim of this research is to take a consumer perception and to find out the interest of consumer about virtual tour and wants to get the impact tourists feel regarding the virtual tour in Nglanggeran Village Research method: This research uses qualitative research through observation, interview, and survey. The author makes observations by participating in virtual tours online and conducting interviews with virtual tour participants to obtain data. Results and discussion: There are three big results obtained that the virtual tour still had much homework to fix and reach because of several factors that obstructed it. The first factor: the virtual tour cannot make visitors feeling enjoy the tour. The second factor: visitors cannot be satisfied with the tour by virtual because there is not interaction directly with nature. The third factor: another visitors are not enjoy the virtual tour because it’s not real. That means virtual tour must be fixed from the internet connection, guide, time duration, facilities, and infrastructure that can make tourists feel the actual travel experience like real and live. Implication: Virtual tours are indeed inviting tourists to carry out tourism activities during a pandemic. However, several factors can minimize the tourist experience in virtual tours. This means that Virtual tours can be used as an alternative for traveling during a pandemic, but the inhibiting factors must be seen so that they can be maximized. Keywords: COVID-19, Virtual Tour, Nglanggeran Tourism Village, Tourist Interest, Travel Experience